Analysis of Publications on Journal Impact Factor Over Time - van Leeuwen, Thed N.; Wouters, Paul F. (Frontiers in Research Metrics and Analytics, 2017)
In this article, we present the results of an analysis that describes the research centered on Journal Impact Factors (JIFs). The purpose of the analysis is to make a start of studying part of the field of quantitative science studies that relates to the most famous and classic bibliometric indicator around and to see what characteristics apply to the research on JIFs. In this article, we start with a general description of the research, from the perspective of the journals used, the fields in which research on JIFs appeared, and the countries that contributed to the research on JIF. Finally, the article presents a first attempt to describe the coherence of the field, which will form the basis for next steps in this line of research on JIFs.